IRPPS e-Publishing service: performance assessment and development of future services - Ruggieri, Roberta; Pecoraro, Fabrizio; Nobile, Marianna; Di Cesare, Rosa (Septentrio Conference Series, 2018)
Over the last decade academic and research libraries have had a fundamental role in supporting Open access practices, in the construction of Institutional repositories, in digitization programs and in the development of additional services for their community. More recently they are moving toward Open science and are identified as one of the main stakeholders in promoting visibility and access of locally-produced scholarship by developing innovative digital publishing service, as well as providing support and guidance on tools and practices in the new open science environment. In line with these open access practices, the IRPPS e-Publishing service was developed with the aim of managing and disseminating its in-house publications. Launched in 2012, the service currently hosts two series – IRPPS Monographs and IRPPS Working Papers – and uses an open source software (Open Journal Systems, OJS) that supports every stage of the publishing process, including the peer-review process. At the beginning of the project a range of services was also developed to assure a uniform and transparent editorial process such as guidelines for submission, editorial and publishing policies aligned with international developments etc. In addition, for each published product a persistent identifier and long-term preservation in the CNR institutional repository, as well as indexing procedures in disciplinary archives and/or academic publishing search engines (i.e. Google Scholar, RePEc, etc.), have been provided contributing to increased availability and visibility of IRPPS scientific outputs. Six years after its launch, it is necessary to make an assessment on strengths and weaknesses of the project. For these reasons the paper intends to describe the analysis carried out to evaluate its impact on both the production of the Institute’s scientific outputs and on their visibility. In particular our object is to investigate the relation between the editorial quality of products connected with already implemented publishing tools (editorial scientific board, international bibliographic codes, copyright/ creative commons etc.) and their impact on managerial, organizational and diffusion activities. For these reasons we analysed the characteristics of published contents in terms of number and type of material, publishing practices and usage statistics. This analysis allows us to gain insight of trends in the increase of published products as well as changes in the types of publications, while publishing practices provide indications on co-authorship and internal and external networking, among other things. This allows us to verify to what extent the editorial improvements introduced by the development of an e-Publishing service have attracted authors to choose this platform to disseminate their work in an open access mode. This is crucial in our case given that the production in Humanities and Social sciences is more locally oriented and mainly monograph-based. Moreover, usage statistics on the basis of data provided by Google analytics and OJS statistical reports, helps analysing readership as well as type of use of IRPPS research products also comparing these results with access of papers previously available on the institutional web page. This analysis provides the basis for the implementation of innovative publishing tools such as altmetrics, and other quantitative and qualitative impact metrics, such as those linked to academic social networks. Moreover, indications from this review can drive the development of an editorial plan related to the digitization of previously published works that have represented important achievements of IRPPS research results. These additional services and the digitization project help and contribute to a larger diffusion and visibility of the scientific research products as well as to a better evaluation process through the use and improvement of alternative metrics together with traditional ones.